Prevalence of Zika and malaria in patients with fever in secondary healthcare facilities in south-eastern Nigeria. (January 2020) - Otu, Akaninyene A; Udoh, Ubong A; Ita, Okokon I; Hicks, Joseph P; Ukpeh, Ido; Walley, John
We describe the frequency of Zika and malaria among patients presenting with fever to secondary health facilities in Cross River State, Nigeria. Using a cross-sectional, stratified survey design, we randomly selected nine facilities and consecutively recruited 100 participants (aged ≥ 1 year) who presented with fever. On testing blood samples using Biocan qualitative lateral flow immuno-chromatographic cassettes for Zika IgG and IgM, 10% were seropositive for Zika virus (ZIKV) IgM, 12% for ZIKV IgG and 20% for ZIKV IgM, IgG or both. Following microscopy of thick films stained with Giemsa for malaria parasites, 55% were positive for malaria and 15% were positive for both malaria and ZIKV IgM, IgG or both. A moderately negative association between urban and rural household location and seropositivity for ZIKV IgM or IgG was found on logistic regression. Our results clearly indicate a high rate of probable ZIKV and malaria co-incidence in Cross River State. Given the high risk of serious fetal outcomes following ZIKV infection, further epidemiological research and surveillance systems for ZIKV are clearly required.